Pelaksanaan Kuliah Kerja Nyata (KKN) FKIP UMN Al-Washliyah Tahun 2025 di Desa Pematang Rambai, Kecamatan Nibung Hangus, Kabupaten Batu Bara: Penelitian - Nadia Oktavia Br. Purba; Anggita Mawaddah Harahap; Isnaini Fadila Putri; Lita Kania; Nanda Fradilla; Arief Hadian; Sugiar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The implementation of the Community Service Program (KKN) by Group 43 students from the Faculty of Teacher Training and Education in Pematang Rambai Village, Nibung Hangus District, Batu Bara Regency, aims to make a real contribution in the fields of education and community empowerment. The main activities carried out include teaching at elementary schools, providing tutoring (BIMBEL) for children, organizing community exercise sessions, as well as designing and installing village signboards. The program was implemented using a participatory approach that actively involved the community in every stage of the activities. The results showed an increase in community participation in literacy activities, improved awareness of healthy living through regular exercise, and the availability of clearer public information facilities through village signboards. This program not only benefits the local community but also serves as a contextual learning experience for students to develop their social, leadership, and collaboration skills.